Orchid inventory in Bantimurung-Bulusaraung National Park, South Sulawesi, Indonesia - DWI MURTI PUSPITANINGTYAS (Society for Indonesian Biodiversity, 2017)
Abstract. Puspitaningtyas DM. 2017. Orchid inventory in Bantimurung-Bulusaraung National Park, South Sulawesi, Indonesia. Biodiversitas 18: 341-350. Bantimurung-Bulusaraung National Park, commonly abbreviated as Babul National Park, is in South Sulawesi. It occupies an area of 43,750 hectares between 119o34'17